Determine criteria for follow-up test defensive basketball junior - Sami, Fares; Kamil, Ali (Journal of Physical Education, 2013)
Longer follow-up defense , one of basketball skills that require the team collective action involving active part and consistent to acquire bouncing balls even not be a chance for members of the team striker acquisition rebounding from the target area and bring it back again , which reduces the chances of scoring, and it enables team members defender of the performance of fast attack and score points for being the increase your chances of success. In light of the foregoing, reflected the importance of research in achieving the objective basis of skill tests that require a circumstance similar to the circumstances of the game with the standard operating procedures for the registration, and that the validity judged by consistency between tests and the extent of achievement of similar conditions for the match . The research problem centered and after seeing the research with respect to skill -up defense and a small number of tests basketball junior , but it was the importance of the problem in addressing this issue through technical tests of skill up defensive serve the junior class , and according to the society original environment of Iraq ( Baghdad ) . Was selected players teams youth team clubs Baghdad and season (2011-2012) and totaling 86 players representing (7) clubs , and after that have been identified tests to skill -up defense was ascertained terms of scientific ( honesty , consistency, objectivity ) as well as the ability to distinguish the homogeneity of the sample , and after getting the results and processed statistically researchers reach his conclusion : the follow-up test that defense has been applied for the first time in the environment of Iraq ( Baghdad ) , and set standards which have Johlha be a standard reference. The recommendations and research focused on the adoption of the follow-up test at defensive ongoing evaluation process , and the use of standards relevant research as a reference standard when the selection process .